Effect of current density on the solid electrolyte interphase formation at the lithium∣Li6PS5Cl interface - Sudarshan Narayanan; Ulderico Ulissi; Joshua S. Gibson; Yvonne A. Chart; Robert S. Weatherup; Mauro Pasta (Nature Communications, 2022)
The interface between the Li metal electrode and inorganic solid electrolyte is crucial for developing reliable all-solid-state Li batteries. Here, the authors show that the Li plating current density distinctly affects the chemistry and morphology of interphase components formed at the interface.